Modulation of insulin-like growth factor-1 receptor and its signaling network for the treatment of cancer: current status and future perspectives - Meizhong Jin; Elizabeth Buck; Mark J. Mulvihill (Oncology Reviews, 2013)
Based on over three decades of pre-clinical data, insulin-like growth factor-1 receptor (IGF-1R) signaling has gained recognition as a promoter of tumorogenesis, driving cell survival and proliferation in multiple human cancers. As a result, IGF-1R has been pursued as a target for cancer treatment. Early pioneering efforts targeting IGF-1R focused on highly selective monoclonal antibodies, with multiple agents advancing to clinical trials. However, despite some initial promising results, recent clinical disclosures have been less encouraging. Moreover, recent studies have revealed that IGF-1R participates in a dynamic and complex signaling network, interacting with additional targets and pathways thereof through various crosstalk and compensatory signaling mechanisms. Such mechanisms of bypass signaling help to shed some light on the decreased effectiveness of selective IGF- 1R targeted therapies (e.g. monoclonal antibodies) and suggest that targeting multiple nodes within this signaling network might be necessary to produce a more effective therapeutic response. Additionally, such findings have led to the development of small molecule IGF-1R inhibitors which also co-inhibit additional targets such as insulin receptor and epidermal growth factor receptor. Such findings have helped to guide the design rationale of numerous drug combinations that are currently being evaluated in clinical trials.